Analysis of mental workload of a nurse in the workplace - Kulczycka, Kinga; Stychno, Ewa (Nursing in the 21st Century, 2012)
ANALYSIS OF MENTAL WORKLOAD OF A NURSE IN THE WORKPLACEAim. The aim of article is presentation of elements which can be burdensome in the work as a nurse.Material and methods. Modified questionnaire “Psychosocial conditions at the workplace” was used in the study. 103 student nurses were surveyed.Conclusions. Analysis of the material gave information about the relationship between the demands of work environment and ability to influence what happens at work.